Organizational vision, values and mission - Scott, Cynthia D. (Crisp Pub. Menlo ParkUS, 1993)
Seeks to help the reader to understand the process of visioning and the importance of individual, group, and organizational values. Shows how these elements fit together to create a coherent, aligned, and productive organization. Teaches how to develop personal, organizational and team missions.